Crude glycerin in diets for feedlot Nellore cattle - Castello Branco van Cleef, Eric Haydt [UNESP]; Bertocco Ezequiel, Jane Maria [UNESP]; D'Aurea, Andre Pastori [UNESP]; Favaro, Vanessa Ruiz [UNESP]; Dourado Sancanari, Juliana Borsari [UNESP] (Revista Brasileira Zootecnia Brazilian Journal Animal Sci, 2014)
Two studies were conducted to evaluate the effects of crude glycerin on feed intake, performance, carcass characteristics, and total digestibility of Nellore bulls. In experiment 1, cattle (n = 30) were fed a control diet without crude glycerin and diets containing 7.5, 15, 22.5, and 30% crude glycerin, for 103 d. Animals were harvested and data of carcass characteristics were collected. In experiment 2, a digestibility trial was performed using indigestible acid detergent fiber (iADF) as internal marker, and five rumen-cannulated steers. Both experiments were conducted as a randomized complete block design and data were analyzed using mixed procedures. In experiment 1 no differences were observed among treatments on dry matter intake, and performance variables. Regarding carcass characteristics, no effect was observed, except for carcass fat estimates, which were greater in treatments with crude glycerin. In experiment 2, crude glycerin promoted a decrease in digestibility of fibrous fractions NDF and HEM, and increased digestibility of crude protein by 6%. Although it caused negative effect on digestibility of fibrous fraction of diets, crude glycerin can be a good energy source for Nellore bulls, since no losses are observed on performance and carcass characteristics when animals are fed up to 30% of this by-product.
Keywords: Beef cattle; by-products; Carcass; digestion; Glycerol